Development Of Educational Crossword Puzzle Games In Arabic Vocabulary Learning For Madrasah Aliyah Students - Siti Naharul Maskanah; Jepri Nugrawiyati; Lailatul Qomariyah; Wildan Nafi'i; Dahlina Dahlina; Faishol Mahmud Adam Ibrahim (Jurnal Al-Maqoyis, 2023)
This research examined the production of an educational crossword puzzle game used to facilitate Arabic vocabulary learning in Madrasah Aliyah. Using the Research and Development Approach by Borg and Gall, the authors used 4 stages to produce the product:  exploration, product development, testing, and finalization. After analyzing the data using methods, the results show a score of 5 (very good category) and validated media experts with a score of 4.8. (Very good category), and limited trials with a score of 4.4 (very good category) and field trials with a score of 4.5 (good category). Further research is needed to expand this vocabulary learning technique beyond this small dataset.